Investigating consumer evaluations about the purchasing of innovative textiles in terms of product interest and benefits - TURHAN, GÜLDEN (Ekin Yayınevi, 2022)
To obtain a sustainable competitive advantage, companies in the national and global markets should direct their activities to new goods and services that create differences. Economic units with high technology and capital accumulation have the opportunity to work more efficiently and create innovations in the market. Nowadays, the main economic resource beyond capital, labor, or natural resources is knowledge. So far, innovation continuously appears in the markets with technological developments in information and communication-intensive sectors such as informatics. \"Innovation\", which has become the most important competitive tool in today\"s economy, is also referred to as innovation. According to the most widely accepted approach of Schmookler (1966), \"An enterprise makes a technical change if it develops a new product or service for itself or uses a new method or input for itself. The enterprise that makes a certain technical change first is the one that makes the innovation, and this action that it does is innovation.\" (Oguzturk, 2003).According to Evans et al. (2010), attitude is a mental state that creates behaviors towards a stimulus. This stimulus can be any product, person, service, brand, idea, physical object, advertisement, event, or symbol as an attitude object. According to the three-component model of attitude that was first added to the literature by Rosenberg and Hovland (1960), attitudes are defined as generalizable structures that consist of beliefs, feelings and behavioral tendencies towards an attitude object. In this model, thoughts and beliefs about the attitude object constitute the cognitive element; emotion and mood represent the affective (or sensory) component, and action intentions represent the behavioral component. Eagly and Chaiken (1993) stated in their studies that it is necessary to understand the underlying cognitive, affective and behavioral processes in order to predict how much the attitude will change. In the process of shaping the evaluations that can occur in different forms, the direct and indirect effects of product interest and benefits on consumer attitude (sensory, cognitive, behavioral evaluations) will be examined in this research.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Tekstil İşletmeciliği ve Yönetimi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Textile Management; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES